Educação em ciências naturais na perspectiva do currículo intercultural : histórias contadas por professores indígenas - Souza, Ivone Mary Medeiros de (2019)
This study is in the field of indigenous school education giving centrality to the natural sciences from the perspective of intercultural curriculum, taking into account that the current national legislation recognizes the right of indigenous peoples to a specific, differentiated, communitarian, bilingual and intercultural pedagogy. Drawing on the theoretical foundations of Cultural Studies for the formulation of bases on intercultural education and on the methodological principles of Oral Thematic History, the research, whose results are presented in this work, had as main objective to analyze histories narrated by indigenous teachers about their experiences in the area of education in the natural sciences, observing marks of dialogues between scientific culture and local culture. The methodology involved the analysis of official documents dealing with indigenous education and semi-structured interviews with four indigenous teachers who work in high school and with practices that are part of the field of Natural Sciences. These teachers belong to the staff of the Tuxaua Luiz Cadete Indigenous State School, located in the Canauanim Community, which is located in the homonymous Indigenous Land and is part of the Wapichana-Macuxi Complex of the Serra da Lua Region. The analysis of the records followed the recommendations of Discursive Textual Analysis, seeking to validate the thesis that indigenous school education, based on the assumptions of the intercultural curriculum, enhances the development of pedagogical practices that resignificance in science education, since they allow the interrelations between scientific culture and local culture, giving meaning to the knowledge schools. The stories told by the indigenous teachers reveal that their pedagogical practices place the school in the place of culture, striving for this institution to constitute itself as space-time of the cultural frontier and to be recognized for accepting difference without hierarchy and without attending to all the demands of capitalism. The teachers' discourses also reveal that the intercultural formation received in their itinerary of formation as teachers provided them with theoretical and methodological foundations that project their practices in the field of interculturality, interdisciplinarity, interlocution between science and knowledge ancestors of the indigenous peoples, in an attempt to achieve the "erasure" of the abyssal line imposed by liberal modern thought.